2004
DOI: 10.1117/12.560034
|View full text |Cite
|
Sign up to set email alerts
|

Integrated optic devices using liquid crystals: design and fabrication issues

Abstract: Integrated optic devices using liquid crystals embedded in optical waveguiding structures have advantages in terms of compactness and high performance. Such devices exploits the high electro-optic effect and the good optical properties of liquid crystals, in particular their high bireffingence and their low absorption, combined with low loss optical waveguides. Optical switches based on ion-exchanged channel glass waveguides and liquid crystals operating in the C-band used for optical communications have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Liquid crystals (LC) are a special class of fluid organic materials that show high intrinsic optical birefringence, stemming from their molecular orientational and/or positional order, which is reminiscent of solid crystalline materials. In addition, their molecular/optical axis reorientates in the presence of applied electric or magnetic fields, which makes them an excellent electro-optic material in a broad range of tunable photonic devices [160,161,162,163,164,165,166,167,168,169,170,171,172,173,174,175,176,177], including numerous examples of LC-PCF for optical switching, tunable filtering and polarization control [178,179,180,181].…”
Section: Sensing Applicationsmentioning
confidence: 99%
“…Liquid crystals (LC) are a special class of fluid organic materials that show high intrinsic optical birefringence, stemming from their molecular orientational and/or positional order, which is reminiscent of solid crystalline materials. In addition, their molecular/optical axis reorientates in the presence of applied electric or magnetic fields, which makes them an excellent electro-optic material in a broad range of tunable photonic devices [160,161,162,163,164,165,166,167,168,169,170,171,172,173,174,175,176,177], including numerous examples of LC-PCF for optical switching, tunable filtering and polarization control [178,179,180,181].…”
Section: Sensing Applicationsmentioning
confidence: 99%
“…Low loss optical channel waveguides can be obtained with different fabrication procedures and different materials, such as SU-8 polymer [15], diffused ion-exchanged on glass and other composite materials [16], [17], [18]. Such waveguiding structures can be efficiently used to fabricate simple and cost effective integrated optic devices working in a wide frequency spectrum for optical communication and sensing systems [19], [20], [21].…”
Section: Introductionmentioning
confidence: 99%
“…However the photonic applications of LCs developed so far are mainly related to free space optics [1]; an excellent review can be found in [2]. Yet limited work exists on LC integrated guided optics [3,4]. Actually packaging and the achievement of a good interface fibre-waveguide have been a hurdle in the development of LC for integrated optics, therefore they have to be addressed specifically.…”
Section: Introductionmentioning
confidence: 99%